Do risk factors for adolescent internalising difficulties differ depending on childhood internalising experiences? - O'Connor, Meredith; Romaniuk, Helena; Gray, Sarah; Daraganova, Galina (My University, 2021)
This study aimed to examine the continuity of internalising difficulties from childhood to adolescence, and determine if the influence of established risk factors on adolescent mental health differed depending on childhood internalising experiences. Data were used from the Kindergarten cohort of the Longitudinal Study of Australian Children (LSAC, N = 4983, est. 2004). Internalising difficulties were measured via parent report on the Strengths and Difficulties Questionnaire (SDQ) at each wave from 4-5 to 14-15 years of age, and defined as symptoms in the borderline or abnormal range (≥ 4). Logistic generalised estimating equations were used to characterise associations between childhood internalising problems (4-9 years) and previously identified risk factors with adolescent internalising difficulties at three time points (10-11, 12-13 and 14-15 years). The risk of internalising problems was elevated at each adolescent age for those who previously experienced internalising symptoms in childhood compared to those who did not (10-11 years: OR 3.67, 95% CI 3.01-4.47, 12-13 years: OR 2.84, 95% CI 2.32-3.46, and 14-15 years: OR 2.33, 95% CI 1.90-2.87). Other known risk factors were found to be associated with adolescent internalising problems as expected. We found no statistical evidence that these associations differed for adolescents who previously experienced internalising symptoms in childhood. Findings of this study confirm the continuity of childhood mental health problems and the role of individual and family characteristics in the aetiology of adolescent internalising difficulties. The same risk factors appear relevant to target for adolescents who first experienced internalising symptoms in childhood.
Keywords: Adolescence; Childhood; Internalising; Longitudinal; Mental health difficulties; Adolescents and youth; Disadvantage, adversity and resilience; Childhood and child development; Health and wellbeing